Aktivitas counting blessing dalam penanganan psychological distress pada pasien kanker payudara - Anak Agung Sri Sanjiwani; Ketut Lisnawati; Anak Agung Gde Oka Widana (University of Merdeka Malang, 2023)
ABSTRACTBreast cancer patients experience recurrent negative thoughts that can cause psychological distress. This problem of psychological distress is also associated with a negative perception of all aspects of cancer, and cancer patients have a tendency to focus only on the negative possibilities that will occur. This study aims to determine the effect of providing counting blessings as one of the gratitude interventions in helping breast cancer patients cope with the psychological distress they experience. This study used a quasi-experimental method with a pre-posttest with control group design involving 22 respondents. The counting blessings activity was delivered by repeatedly asking respondents (experimental group) to write down five things for which they were grateful each day. Psychological distress was measured using the Hospital Anxiety Depression Scale (HADS) questionnaire. The results of this study indicate that there is a significant effect on the level of psychological distress (anxiety and depression) of breast cancer patients after being given the counting blessings activity (p=0.000 for anxiety and p=0.002 for depression). The efforts made by patients to focus on the positive aspects of daily life are beneficial in helping them to re-interpret what is happening in their lives.ABSTRAKPasien kanker payudara mengalami berbagai pikiran negatif berulang yang dapat menyebabkan psychological distress. Permasalahan psychological distress ini juga melibatkan adanya persepsi negatif terhadap segala aspek dari penyakit kanker dan pasien kanker cenderung hanya fokus pada kemungkinan negatif yang akan terjadi. Penelitian ini bertujuan untuk mengetahui pengaruh dari pemberian aktivitas counting blessing sebagai salah satu gratitude intervention dalam membantu pasien kanker payudara menangani psychological distress yang dialami. Penelitian ini menggunakan metode quasi eksperimen dengan rancangan pre-posttest with control group yang melibatkan 22 responden. Aktivitas counting blessing diberikan dengan meminta responden (kelompok eksperimen) secara berulang untuk menuliskan lima hal yang disyukuri setiap harinya. Kondisi psychological distress diukur menggunakan kuisioner HADS (Hospital Anxiety Depression Scale). Hasil penelitian ini menunjukkan bahwa terdapat pengaruh yang signifikan pada tingkat psychological distress (kecemasan dan depresi) pasien kanker payudara setelah diberikan aktivitas counting blessing (p=0,000 kecemasan dan p=0,002 pada depresi). Upaya yang dilakukan pasien dalam memberikan perhatian pada aspek positif dalam kehidupan sehari-hari memberikan manfaat dalam membantu pasien memaknai ulang apa yang telah dijalani dalam kehidupannya.